Advanced Concepts in Endocarditis - Firstenberg, Michael S. (IntechOpen, 2018)
Endocarditis is a disease process that involves an infection of the heart, cardiac structures, or implantable cardiac support devices and can be a difficult clinical problem. As patients get older and have more comorbidities, their risks for infection increase. In addition, the growing problem of intravenous substance abuse has led to a considerable increase in these patients developing endocarditis. Advances in medical technology have facilitated diagnosis and management, particularly with greater emphasis on early surgical intervention. Nevertheless, success requires a team approach and individualization of care in the setting of very complex medical, surgical, and ethical problems. The goal of this book is to illustrate some of the evolving challenges and controversies in managing these very complex and often extremely sick patients.